Field evidences for the positive effects of aerosols on tree growth. (28th June 2018) - Wang, Xin; Wu, Jin; Chen, Min; Xu, Xiangtao; Wang, Zhenhua; Wang, Bin; Wang, Chengzhang; Piao, Shilong; Lin, Weili; Miao, Guofang; Deng, Meifeng; Qiao, Chunlian; et al.
Abstract: Theoretical and eddy covariance studies demonstrate that aerosol‐loading stimulates canopy photosynthesis, but field evidence for the aerosol effect on tree growth is limited. Here, we measured in situ daily stem growth rates of aspen trees under a wide range of aerosol‐loading in China. The results showed that daily stem growth rates were positively correlated with aerosol‐loading, even at exceptionally high aerosol levels. Using structural equation modeling analysis, we showed that variations in stem growth rates can be largely attributed to two environmental variables covarying with aerosol loading: diffuse fraction of radiation and vapor pressure deficit (VPD). Furthermore, we found that these two factors influence stem growth by influencing photosynthesis from different parts of canopy. Using field observations and a mechanistic photosynthesis model, we demonstrate that photosynthetic rates of both sun and shade leaves increased under high aerosol‐loading conditions but for different reasons. For sun leaves, the photosynthetic increase was primarily attributed to the concurrent lower VPD; for shade leaves, the positive aerosol effect was tightly connected with increased diffuse light. Overall, our study provides the first field evidence of increased tree growth under high aerosol loading. We highlight the importance of understanding biophysical mechanisms of aerosol‐meteorology interactions, and incorporating the different pathways of aerosol effects into earth system models to improve the prediction of large‐scale aerosol impacts, and the associated vegetation‐mediated climate feedbacks. Abstract : Aerosols could significantly alter terrestrial carbon uptake, but field evidence for the aerosol effect on tree growth is limited. Our study provides the first observational evidence of aerosol's positive effects on tree stem growth based on in‐situ measurements. The increased stem growth can be attributed to higher canopy photosynthesis induced by diffuse radiation fertilization effect and the accompanying lower vapor pressure deficit. Our study points out that the co‐varying meteorological conditions have an important role in modulating plant carbon assimilation under aerosols conditions, and highlights the importance of incorporating these mechanisms into earth system models for better simulating large‐scale climate‐vegetation interactions.